2008
DOI: 10.1029/2008jc004835
|View full text |Cite
|
Sign up to set email alerts
|

Relative and absolute sea level rise in western Canada and northwestern United States from a combined tide gauge‐GPS analysis

Abstract: [1] Empirical studies and climate models suggest large variations of absolute sea level (ASL) changes between oceanic basins. Such potential variations raise concern on the applicability of global mean ASL predictions to specific regions and on estimates of relative sea level (RSL) hazards. We address this issue for the western Canada and northwestern United States coastline by estimating the 20th century ASL rate using a combination of 34 colocated tide gauge and Global Positioning System (GPS) stations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 39 publications
5
67
0
Order By: Relevance
“…We suggest two factors that may have contributed to this result. a consequence of tectonic uplift in the region (Mazzotti et al 2008). Therefore, the mechanism of vertical accretion may be different from that observed in marshes experiencing rising sea level.…”
Section: Low Marsh Car 10mentioning
confidence: 86%
“…We suggest two factors that may have contributed to this result. a consequence of tectonic uplift in the region (Mazzotti et al 2008). Therefore, the mechanism of vertical accretion may be different from that observed in marshes experiencing rising sea level.…”
Section: Low Marsh Car 10mentioning
confidence: 86%
“…These results are independent of the eustatic or regional sea-level changes. Similarly, Mazzotti et al (2008) reported upward vertical velocities of between 1 and 3 mm a À1 for coastal sites throughout the Cascadian region, but did not attempt to partition the signal into interseismic strain and isostatic rebound. Inland sites tended towards lower vertical velocities, with slight subsidence in some cases (to À1 mm a À1 ).…”
Section: Regional Tectonic Regimementioning
confidence: 93%
“…The dune complex is located toward the southern end of a 10 km-long embayed beach within Wickaninnish Bay, which has a southwest aspect to the Pacific Ocean, a mesotidal range (spring tide rangẽ 4.2 m), and is exposed to energetic wave conditions (average winter significant wave height of 2.47 m and period 12.07 s). Beaches in the area are wide, dissipative and backed by 1 to 5 m high vegetated foredunes that are prograding at a rate of approximately 0.2 m a −1 (Heathfield and Walker, 2011) in response to regression of relative sea level in response to crustal uplift along the Cascadia subduction zone (Mazzotti et al, 2008). The foredunes are backed by one of the largest active transgressive dune complexes on Vancouver Island.…”
Section: Regional Settingmentioning
confidence: 99%